AI Technology and Academic Writing: Knowing and Mastering the “Craft Skills” - Storey, Valerie A (International journal of adult education and technology (Print), 2023)
Evidence shows that artificial intelligence (AI) has become an important subject in academia, representing about 2.2% of all scientific publications. One concern for doctoral programs is the future role of AI in doctoral writing due to the increase in AI-generated content, such as text and images. Apprehensions have been expressed that the use of AI may have a negative impact on a doctoral student's ability to think critically and creatively. In contrast, others argue that using AI tools can provide various benefits resulting in rigorous research. This conceptual article first discusses the developing relationship between AI and dissertation writing skills. Second, the article explores the origins of the traditional dissertation and outlines 21st-century dissertation options which reflect contextual needs and utilization of AI. Third, identified writing challenges are highlighted before turning to an in-depth examination of AI-generated tools and writing craft skills required to complete the five chapters of a traditional dissertation.